Ketogenic diet and β-hydroxybutyrate in osteoporosis: current progress and controversy - Luo, Changfang; Dai, Zhuojun; He, Wanhong; He, Yanqiu; Yang, Ping; Huang, Mengting; Li, Junle; Xu, Yong; Huang, Wei (Frontiers in Nutrition, 2025)
Diet has been proven to have significant impacts on the pathogenesis and treatment of osteoporosis. This review attempts to elucidate the current progress and controversy surrounding the ketogenic diet (KD) and β-hydroxybutyrate (BHB) in osteoporosis and offers a novel perspective on the prevention and treatment of osteoporosis. The ketogenic diet has been broadly used in the treatment of epilepsy, diabetes, obesity, and certain neoplasms by triggering ketone bodies, mainly BHB. However, in most osteoporosis-related clinical and preclinical studies, the ketogenic diet has demonstrated the detrimental effects of inhibiting bone accumulation and damaging bone microarchitecture. In contrast, BHB is thought to ameliorate osteoporosis by promoting osteoblastogenesis and inhibiting osteoclastogenesis. The main purpose of this review is to summarize the current research progress and hope that more basic and clinical experiments will focus on the similarities and differences between ketogenic diet (KD) and BHB in osteoporosis.